Wissenschaftskommunikation in Leichter Sprache? Eine Bestandsaufnahme der Verwendung von Leichte-Sprache-Angeboten in den Webauftritten deutscher Forschungs- institutionen und Hochschulen - Hanauska, Monika (Linguistik Online, 2022)
Recent research on the impact and reception of science communication pointed out, that marginalized groups in society like people with mental or learning disabilities or people with limited language skills often remain unconsidered by conventional measures of communicating scientific content (Humm/Schrögel/Leßmöllmann 2020). Easy reading concepts might be a helpful approach to a more inclusive mode of science communication. The paper evaluates if German science institutions and universities offer easy reading versions on their websites to enable the above-mentioned groups to access fundamental scientific information. In a second step it analyses how these easy reading versions have been formally implemented and to what extent the requirements of the Federal Ordinance on Accessible Information Technology (BITV 2.0) have been followed. The paper aims to give a first overview on the efforts of scientific institutions to address marginalized groups and to point out deficits of these efforts.